Penerapan Nilai-Nilai Akhlak Peserta Didik Melalui Kegiatan Kepramukaan - Fajar Setiawan; Murniyetti Murniyetti (An-Nuha, 2023)
This study aims to describe the application of moral values ​​to students through scouting activities at SMKN 1 Sijunjung. This type of research is qualitative research using descriptive method. The research data was obtained from interviews with research informants. The data collection tool is a mobile phone. The technique of checking the validity of the data in this study was carried out by triangulation. The results of the research are to analyze and to reveal the results of research findings related to the application of the moral values ​​of students through scouting activities at SMKN 1 Sijunjung. The results of the application of the moral values ​​of students through scouting activities at SMKN 1 Sijunjung in shaping the character of students experience slight deviations such as the presence of students who are less disciplined in entering school, entering class, or in carrying out prayer services.